Tetanus in School Age Children Seen at the University of Port Harcourt Teaching Hospital: A Need for Booster Doses of Tetanus Vaccine - B. A. Alex-Hart; D. LongJohn (Archives of Current Research International, 2020)
Background: Tetanus still causes significant morbidity and mortality amongst children in Nigeria despite decades of immunisation with tetanus vaccine. Objectives: To determine the prevalence, case fatality rate and predictors of fatality amongst school age children treated for tetanus at the University of Port Harcourt Teaching Hospital. Materials and Methods: This was a retrospective study of all children aged 4 to 17 years treated for tetanus at the University of Port Harcourt Teaching Hospital between January 1, 2009 and December 31, 2019. Data was obtained from the case notes and ward registers. Socio-demographic characteristics, presenting complaints, incubation period, onset interval, number of Diphtheria, Pertussis and Tetanus (DPT) vaccine received at infancy, treatment outcome, duration and cost of hospital stay were obtained, entered into a spread sheet and analysed with SPSS version 20. Results are presented in tables and percentages. The level of significance was set at P value <0.05. Results: During the period under review, there were 53 children aged 4 to 17 years treated for tetanus, accounting for 0.3% of the total admission. The mean age was 10.79±3.35 years. There were 33 (62.26%) males and 20 (37.74%) females. Majority 26 (49.06%) of the children were of low socioeconomic class. The commonest 28(52.8%) route of infection was broomstick injury. Majority 32(60.3%) of the children were not immunised in infancy. The mean incubation period was 7.34±4.21 days and the mean onset interval was 8.87±10.44 hours. The two most common symptoms were generalized spasms 49 (21.03%) and trismus 47 (20.17%). Short incubation period (≤4 days) and short onset interval (≤4 hours) were significantly associated with higher death rates (p=0.0002; p=0.012). Patients with short incubation period of ≤4 days and short onset interval of≤ 4 hours are more likely to die (p=0.0002; p=0.012). Conclusion: There was a high tetanus case fatality rate amongst school age children at University of Port Harcourt. Short incubation period and onset interval were associated with higher mortality. Booster doses of TT containing vaccines should be administered to primary and secondary school children in Port Harcourt to curb the menace.